Community-associated Clostridium difficile infection in emergency department patients in Western Australia - Collins, D.; Selvey, Linda; Celenza, A.; Riley, T. (2017)
Clostridium difficile infection (CDI) is primarily associated with hospitalised patients, however, community-associated CDI (CA-CDI) has increased in Australia. We aimed to investigate the epidemiology and outcomes of CA-CDI cases presenting to hospital emergency departments in Western Australia (WA). A retrospective case-control study of CA-CDI cases presenting at six emergency departments in WA from July 2013 to June 2014 was performed. Clinical signs, recent medication, hospitalisations and potential risk factors for CA-CDI were investigated for cases (n = 34) and unmatched controls (n = 62) who were infected with another gastrointestinal pathogen, including Campylobacter spp., Salmonella spp., Aeromonas spp., Shigella sonnei and Escherichia coli O157. Elevated white cell count (31.3% vs 8.2%, p < 0.01), female gender (67.6% vs 41.9%, p < 0.05), age =65 years (41.2% vs 21.0%, p < 0.05) and antimicrobial use in the previous month (41.2% vs 11.3%, p < 0.01) were significantly more frequent among cases compared to controls. After multivariable analysis, antibiotic use (odds ratio 8.49, 95% confidence interval 2.75–26.21) and age =65 years (3.03, 1.05–8.75) were significantly associated with CA-CDI. Ribotype (RT) 014/020 was most common (40.7%) among 27 C. difficile isolates followed by RTs 002 (14.8%), 001, 056 and 244 (all 7.4%). CA-CDI was associated with advanced age and recent antibiotic use compared to those infected with other gastrointestinal pathogens. RT 014 has also recently been found at high prevalence in public lawn spaces, and previously RT 014 strains from humans and pigs in Australia were closely genetically related, suggesting CA-CDI may be linked with these community reservoirs.